Diversity of Fish Types and Water Quality in the Waters of Curug Gumawang, Curuggoong Village, Padarincang District, Serang-Banten District - Hermawan Hermawan (Multidisciplinary Journal of Social Sciences and Humanities, 2025)
This research was carried out in the Gumawang Waterfall Area in Padarincang Village, Padarincang District, Serang-Banten Regency. The research was carried out to determine the diversity of fish species found in the Gumawang Waterfall. The results of this research were that 7 types of fish were obtained, including tilapia, goldfish, wader, catfish, eel, chana and sili fish. The most abundant fish in the Gumawang waterfall area is the wader fish with a total of 35 fish. Fishing is carried out at 3 points. The fish species diversity index value at Curug Gumawang was 1.523840153, this result shows that it is in the "Medium" category. Meanwhile, measuring the water quality at Gumawang Waterfall shows that the water temperature is around 23oC with a water clarity level of 30, and the water diameter is around 1-1.5 meters or as big as an adult's chest.